A latent class analysis of community-based rehabilitation needs among Chinese older adults: a mixed study protocol - Xu, Lei; Xue, Caixiu; Yang, Ke; Chen, Lingyun; Chen, Xidong; Xie, Xiaohui; Wang, Jia; Wang, Xueting; Wang, Lianhong (Frontiers in Public Health, 2024)
Background: Geriatric diseases (e.g., chronic diseases and geriatric syndromes) may result in impaired physical performance and a decline in the quality of life. The results of these Previous studies indicated have reported positive effects of comprehensive community-based rehabilitation (CBR) services on physical and social functioning and psychosocial well-being. However, to provide adequate and personalized rehabilitation services, it is essential to understand the needs of the elderly population. There have been no studies on the need for CBR in elderly populations that consider their heterogeneity. Therefore, high-quality studies are required to recognize the heterogeneity and latent classes of CBR needs in elderly population groups. This study aims to identify the heterogeneity of the rehabilitation needs of older adults in the community and explore whether older adults with similar characteristics have similar needs through a cross-sectional survey and latent class analysis (LCA) to provide support for personalized rehabilitation services.The study will be structured into four phases. The first phase will focus on constructing a comprehensive questionnaire to assess rehabilitation needs. In the second phase, a pilot study will be conducted to evaluate the reliability and validity of the completed questionnaire. This step ensures the robustness of the instrument for data collection. The third phase will involve cross-sectional surveys using the finalised questionnaires to collect the necessary data from the targeted population.The fourth phase will focus on conducting LCA to determine the CBR needs of older adults of the elderly population.The results of this study will provide novel and critical information for better understanding the rehabilitation needs, potential categories, and influencing factors of older adults in the community. The study will be conducted in Guizhou Province in western China, where economic and social development is relatively low, and the results will inform and benefit other regions and developing countries facing similar challenges. However, because of the complete social security and rehabilitation service systems in developed areas, our research results may not fully reflect the 2 situation in these areas. Future studies may need to be conducted in places with different levels of social development.